2005
DOI: 10.1650/7614
|View full text |Cite
|
Sign up to set email alerts
|

Transformations at High Latitudes: Why Do Red Knots Bring Body Stores to the Breeding Grounds?

Abstract: Brown Pelicans (Pelecanus occidentalis) plunge dive into water to capture fish with highly distensible pouches. During prey capture, the pouch may expand to hold 11 L of water and the mandibular rami may bow from a resting position of 5 cm to over 15 cm. We compared mineralization of two bending regions of the mandible with a nonbending region, and examined cross-sectional morphology to determine if mineral content and shape play a role in mandibular bending. A rostral bending zone, adjacent to the mandibular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 53 publications
(76 reference statements)
3
44
0
Order By: Relevance
“…On theoretical grounds, shorebirds, of which many species undertake similarly long or even longer migrations than geese, are less likely to use this strategy, because of their much smaller size (Klaassen 2003). Empirical studies comparing isotope signatures of eggs with body stores accumulated during migration (Morrison and Hobson 2004) and chicks with those of feathers grown by their parents on wintering or spring staging areas (Klaassen et al 2001), have confirmed that arctic shorebirds generally produce eggs mostly from nutrients collected after arrival on the breeding grounds ('income breeders'; (Klaassen et al 2001;Morrison and Hobson 2004;Morrison et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On theoretical grounds, shorebirds, of which many species undertake similarly long or even longer migrations than geese, are less likely to use this strategy, because of their much smaller size (Klaassen 2003). Empirical studies comparing isotope signatures of eggs with body stores accumulated during migration (Morrison and Hobson 2004) and chicks with those of feathers grown by their parents on wintering or spring staging areas (Klaassen et al 2001), have confirmed that arctic shorebirds generally produce eggs mostly from nutrients collected after arrival on the breeding grounds ('income breeders'; (Klaassen et al 2001;Morrison and Hobson 2004;Morrison et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of being channelled into eggs, nutrient stores carried to the breeding grounds may also be metabolised during the period directly after arrival, when food availability is limited and unpredictable owing to weather and snow conditions (Morrison 1975;Sandberg 1996;Baker et al 2004;Morrison et al 2005). Such stores may be important for survival and reproduction: unusually cold early summers in 1972 and 1974 caused extensive mortality of adult Red Knots Calidris canutus in northern Greenland and Canada (Morrison 1975;Boyd and Piersma 2001), and birds departing from Iceland with below-average mass suffered more than heavier birds (Morrison 2006;Morrison et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations